PENGGUNAAN LIMBAH KERAMIK DAN SERBUK KACA SEBAGAI BAHAN STABILISASI TANAH RAWA - Irma Sepriyanna; Fitri Khairani (FORUM MEKANIKA, 2016)
Marshland is soft soils containing clay, silt and peat. Clay / silt are cohesive plastic which has the properties coherency between the grains and capable of continuously formed permanently with a relatively moderate pressure without rupturing. However, clay or silt becomes inconsistent / unstable to loading, resulting in a high settlement when loaded (instability). Marshland has unstable behavior which is necessary to improve. One of chemically improvement can be done by recovering waste glass bottles and ceramic shards waste as a stabilizing agent. Waste glass bottles and ceramic shards of waste recycled in a crushed glass powder and ceramic powder which serves as a filler and a binder. Based on test results obtained optimum value percentage value addition of powdered glass and ceramic powder is on the ground with a mixture of 10% and 10% glass powder with a ceramic powder curing 7 days . The soil with a mixture of 10% and 10% glass powder with a ceramic powder curing 7 days has a value of water content of 44.81%, 1.40 specific gravity, liquid limit of 56.92%, 30.36% plastic limit, shrinkage limit 26 , 49%, 26.56% plasticity index, CBR 36.33%. This shows that the soil with the CBR value (CBR 3% - 7%) can be used as a subgrade layer for local residential streets or roads with low traffic